Peran Peran Mahasiswa dalam Program Asistensi Mengajar di TK Tri Murti Surabaya - Alfiatur Rakhma, Syavrilia; Nur Chamidah (Universitas Hamzanwadi, 2024)
The Teaching Assistance Program is an implementation of the Merdeka Belajar Kampus Merdeka (MBKM) initiative aimed at enhancing education quality while providing practical experience for university students. This study documents the implementation of teaching assistance by undergraduate Statistics students of Universitas Airlangga at TK Tri Murti Surabaya. Through observation, teaching, and mentoring activities, students contributed to improving the learning process and addressing individual needs of early childhood students, including supporting their cognitive, social, and motoric development. The results show dual benefits: accelerating students’ learning comprehension and providing university students with valuable experience in classroom management and interaction with diverse student backgrounds. This program highlights the effectiveness of collaboration between higher education institutions and educational organizations in supporting equitable early childhood education quality